Situation Report: Poland, 21 November 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Poland and the Bulgarian CP Congress Collective Communist Policy towards Bonn? End of Church Millennium Celebrations Senator Clark's Polish Visit Poland's Economic Ties with Italy Becoming Stronger